Onbewoonde en bewoonde huizen. Functieveranderingen in de Nijmeegse binnenstad tussen 1860 en 1910 (Bulletin KNOB, 1995)
The article deals with the functions developing in and from private houses during the period when the physical decay of the town centre was becoming manifest. Nijmegen serves as an example because uniform sources of building inspection authorities are available. The irreversible process of decay in the twentieth century, resulting in large-scale demolition during the sixties and seventies, made research into the initial phase of the declining residential function desirableAround 1880 only 1,2% of the built-up area in the town centre of Nijmegen had no residential function (total number of houses/premises 3.161). In the period 1880-1910 there was a great increase in economic activity; the development of the residential function was lagging behind. These functional changes occurred in a physically scarcely changing stock of buildings.From a housing research carried out in 1907 it is evident that there were 579 houses in the town centre with only one single room and 1457 houses with two rooms. In that period approximately 44% of the residents of the town centre lived in houses which were unfit for habitation. The advice of the municipal Board of Health in 1905 to improve public housing systematically by new-construction projects outside the town centre, as well as by reconstruction of building blocks within the town, were not acted upon.Public housing in the twenties and thirties was exclusively aimed at urban expansion; it was not until after World War II that redevelopment and reconstruction of the town centre was put on the political agenda.